(untitled) (Jurnal Peternakan Lingkungan Tropis, 2024)
This study aims to determine the impact of fermentation with several different types of microbial starters on the physical quality of lai fruit waste (Durio kutejensis). Lai fruit is an endemic plant from East Kalimantan Province whose waste consists of skin and seeds after humans have consumed the pulp. Lai fruit waste can pollute the environment if not managed properly. Fermentation is a feed processing technology that improves nutritional quality and increases shelf life. The types of microbial starters used in the fermentation of lai fruit waste in this study were Aspergillus niger, Effective Microorganisms 4 (EM4), and Phanerochaete chrysosporium. Fermentation was carried out for 21 days under anaerobic conditions. Parameters observed in the physical quality test included: degree of acidity (pH), fermentation temperature, texture, color, shrinkage, aroma, and percentage of fungus. Data were analyzed with a complete randomized design (CRD) with 4 treatments and 3 replications, including P1: fermented lai fruit waste without microbial starter, then for P2, P3, and P4 added different microbial starters A.niger, E. microorganisms 4 and P. chrysosporium. This study concluded that the addition of microbial starters in the fermentation of lai fruit waste produced the best physical quality when compared to the control (P1). Fermented lai fruit waste has the potential to be used as a raw material for ruminant feed.